Executive Functions May Predict Outcome in Deep Brain Stimulation of Anterior Nucleus of Thalamus for Treatment of Refractory Epilepsy - Järvenpää, Soila; Rosti-Otajärvi, Eija; Rainesalo, Sirpa; Laukkanen, Linda; Lehtimäki, Kai; Peltola, Jukka (Frontiers in Neurology, 2018)
Background: Deep brain stimulation (DBS) of the anterior nucleus of thalamus (ANT) is an emerging treatment option for patients suffering from refractory epilepsy. ANT has extensive connections with hippocampus and retrosplenial cingulum, areas associated mainly with spatial memory and with anterior cingulum which is important in executive functions. As refractory epilepsy is often associated with cognitive decline and neuronal damage, the decreased connectivity between ANT and remote structures might impact on the effects of DBS. Objective: We hypothesized that the neuropsychological profile could reflect the connectivity of ANT and further predict the efficacy of ANT DBS. We measured the cognitive performance of patients with refractory epilepsy with DBS to evaluate whether neuropsychological profiles could reflect the connectivity of ANT and further predict the efficacy of ANT DBS. Method: Sixteen patients with refractory epilepsy treated with ANT DBS with at least 2 years of follow-up were included in the study. Patients underwent a neuropsychological evaluation as a part of the protocol and their clinical outcome was determined by seizure frequency in the last 6 months compared to baseline. The patients were classified as responders if there was a ≥ 50% reduction in the frequency of the predominant seizure type, otherwise as nonresponders. Results: There were 12 responders and 4 nonresponders for ANT DBS treatment in the study population. Nonresponders performed worse than responders in neuropsychological tasks measuring executive functions and attention, such as the Trail Making-Test. Conclusions: Better executive functions and attention seemed to predict improved clinical outcome after the ANT DBS surgery. Based on our preliminary descriptive findings and the anatomical connectivity hypothesis, we suggest that deficits in executive functions may relate to an inferior outcome. This finding might offer new tools for refining the selection of patients with refractory epilepsy scheduled to undergo ANT DBS surgery. Moreover, it highlights the need for further investigations of neural connectivity in epilepsy.